Distribution Features of Flow Patterns and Pressure Pulsations of Pump-Turbine in Five Operating Modes on the Four-Quadrant Plane - Hu, Dongliang; Cheng, Yongguang; Zhang, Pengcheng; Wang, Xi; Ding, Jinghuan; Zhang, Xiaoxi (Frontiers in Energy Research, 2022)
To meet the demand of the power grid for flexible regulation, pump turbines have to frequently and fleetly stop, start, and transition between different modes, causing many instability problems. To solve the problems, understanding the complex flow and pressure pulsation features in different working conditions is the prerequisite. In this study, the flow patterns, pressure pulsations, cavitation characteristics, and runner forces of a prototype pump-turbine working under the five operating modes were displayed and analyzed based on computational fluid dynamics simulations. It is shown that when working points are near the pump and turbine design working points, the flow is smooth, with small pressure pulsation and without cavitation; however, when working points deviate from the optimal ones, flow patterns become worse and cavitation appears. In the pump-brake mode, the flow hits the runner blades violently, causing obvious pressure and runner force fluctuations. In the hump region, the flow has a strong impact on the guide vanes, and the rotating stall vortices are apparent in the vane area. In the S-shaped region, pressure pulsations are the highest with prominent rotor–stator interaction and rotating stall. Under similar working conditions, a larger guide-vane opening corresponds to a larger pressure pulsation amplitude. On the spatial distribution, the largest pressure pulsations happen in the vaneless space.